Analisa Pengaruh Arus Bocor Terhadap Total Harmonic Distortion Pada Isolator 150 kV Yang Terkontaminan Lumut Menggunakan Transformasi Fourier - Rachmat Deska Saputra; Sitti Amalia; Yusreni Warmi; Sepannur Bandri; Andi M Nur Putra (G-Tech: Jurnal Teknologi Terapan, 2024)
This study investigates the Total Harmonic Distortion (THD) of 150 kV insulators contaminated with moss based on leakage current patterns with three variations of test voltages, namely 10,578 V, 21,063 V, dan 30,569 V. The tests were conducted experimentally at the High Voltage Laboratory of Gajah Mada University with a temperature of 28.2 °C dan humidity of 57.8%. The test was conducted experimentally at the High Voltage Laboratory of Gajah Mada University with a temperature of 28.2°C dan humidity of 57.8%. The analyzed parameters include waveform, frequency spectrum (FFT), dan THD, which were calculated using Fast Fourier Transform (FFT) through NI DIAdem software. The test results showed no strong relationship between leakage current dan THD. At a leakage current of 0.103 mA, the resulting THD is 21.84%, while at a current of 0.207 mA produces a THD of 18.27%, dan 0.306 mA produces a THD of 36%. Based on the IEEE STD 519-2014 stdanard, THD on 150 kV insulators contaminated with moss exceeds the maximum limit of 15%, so this insulator is not safe to use on the Koto Panjang-Payakumbuh transmission line.